Association Between Chronic Obstructive Pulmonary Disease and Type 2 Diabetes: A Systematic Review and Meta-Analysis. (3rd September 2018) - Malte Rasmussen, Søren; Brok, Jesper; Backer, Vibeke; Francis Thomsen, Simon; Meteran, Howraman
Abstract: Background: Chronic obstructive pulmonary disease (COPD) has been associated with an increased risk of type 2 diabetes (T2D). However, the mechanisms linking COPD and T2D is not fully understood and contradicting results are reported in the literature. Aim: The aim of this study is to investigate whether COPD is associated with an increased risk of T2D. Methods: A systematic review and meta-analysis of cohort and case-control studies were performed. Search for studies and data extraction was carried out by two authors independently. Study quality was assessed by NOS. Adjusted data were pooled using the random effects model to calculate summary odds ratios (ORs) with corresponding 95% confidence intervals (CIs). Results: We identified four cohort studies and three case-control studies with a total of 1, 369, 560 participants of whom 42, 716 were COPD patients. The quality of the studies was acceptable, with an average on 7.7 indicating overall good study quality. The meta-analysis on adjusted data from all seven studies showed that the COPD group had a higher risk of T2D compared with the non-COPD group: random effect OR = 1.17 (1.01–1.35), p  = 0.03. No heterogeneity was found I 2  = 0%. When including only studies diagnosing both COPD and T2D according to recommended guidelines the association did not remain statistically significant, OR =1.17 (0.96–1.42), p  = 0.12. Conclusion: This systemic review and meta-analyses showed that the association between COPD and T2D might be influenced by the diagnostic method and should be further investigated in studies using diagnostic definition according to guidelines. Nevertheless, physicians should be aware of comorbidities in COPD patients.